(untitled) (International Journal of Engineering and Computer Science, 2017)
Blind equalizers may be implemented with linear prediction error filters (LPEF) but the delay (D) cannot be controlled with onestep predictors to minimize the mean square error (MSE). Consequently, multi-step prediction error filters (MSPEF) has been suggested as a solution to the problem. In this paper, a blind equalizer composed of the Godard algorithm (CMA) cascaded with MSPEF is proposed (CMA_MSPEF), and we extract the optimum value of step for multi-step prediction blind equalizer. Simulation results show comparable improvements of the proposed equalizer relative to the LPEF or the MSPEF equalizers with optimum step.